Long‐term follow‐up with filter paper samples in patients with propionic acidemia. Issue 1 (27th September 2020) - Stanescu, Sinziana; Belanger‐Quintana, Amaya; Fernández‐Felix, Borja Manuel; Pérez‐Cerdá, Celia; Merinero, Begoña; Ruiz‐Sala, Pedro; Arrieta, Francisco; Martínez‐Pardo, Mercedes
Abstract: Background: Propionic acidemia (PA) is an inherited disorder caused by deficiency of propionyl CoA carboxylase. Most patients with this disorder are diagnosed during the neonatal period because of severe metabolic acidosis and hyperammonemia. Patients are required to undergo blood and urine analysis at least 3 to 4 times per year, depending on age and metabolic control. Methods: We designed a prospective study in which we investigated the results from blood and urinary samples collected monthly in filter paper from 10 PA patients followed in a single metabolic reference center from January 2015 to September 2017. The aim of this study was to evaluate the usefulness of filter paper samples in the follow‐up of the PA patients. Results: During the follow‐up period, 163 dried blood spot (DBS) and 119 urine dried spot samples were analyzed and compared with 160 plasma and 103 liquid urine specimens; 64 specimens of plasma were analyzed for odd‐numbered long‐chain fatty acids (OLCFAs). A total of 40 metabolic crises, 18 of them with hyperammonemia were documented. We observed a strong correlation between the filter paper and the urine/plasma samples for the main PA parameters both in stable metabolic conditions as well as in acute decompensations. Also, there was a strong correlation between OLCFAs measured in plasma and quantification of odd number acylcarnitines in DBS. Conclusions: We conclude that filter paper blood and urinary samples can be used for the follow‐up of the patients with PA, correctly reflecting their metabolic situation.